Teacher Planning Strategies in Creating Creative and Interactive Classroom Learning - Maulana, Yoga; Kurniasari, Anggi; Dewi, Tri Ratna; Najib, Khasbi Ainun (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, Jurusan Tarbiyah dan Keguruan, Sekolah Tinggi Agama Islam Negeri Majene, 2025)
This research aims to explore and analyze the planning strategies used by teachers in creating creative and interactive classroom learning. The main focus of this study will be more emphasis on how the teacher's planning readiness in integrating methods, media, and approaches that are in accordance with student characteristics and learning objectives. This study collected descriptive data through observation and in-depth interviews with several teachers at SDN 1 Gumawang. The method used in this study is the Case Study method, as it allows to understand the context and details of the implementation of learning planning strategies in more depth. The results of this study show that good planning and oriented to the characteristics of each student is proven to be able to create a more lively and meaningful classroom atmosphere, increase learning motivation, and strengthen the active involvement of each student in the learning process. With the use of the right planning strategies, teachers can be the driving force in creating learning that is not only informative, but also creative and interactive.